CONSENT FOR THE CONCLUSION OF THE CONTRACT - Radomirović, Ivana; Radomirović, Ivana (Glasnik Advokatske komore Vojvodine, 2023)
Summary            The subject of this paper is the consent of the third party to the conclusion of the contract. The current lack of interest in the legal doctrine regarding the institution of third-party consent to the conclusion of the contract is a consequence of its normative disunity. Bearing in mind the large number of cases in which the consent of a third party is required for the conclusion of the contract, the consent is regulated sporadically in certain parts of the regulations that govern separate contracts for which conclusion the consent of the third party is required. Therefore, the paper deals with the most frequent contracts in legal transactions, namely contracts in which persons with limited ability participate, as well as the contracts on sublease and sublicense. The subject of this paper is the analysis of the current legislation regulating consent in the Republic of Serbia, as well as the analysis related to the form, legal nature and consequences of the absence of consent for the conclusion of the contract. Furthermore, the paper presents a comparative legal analysis of the relevant regulation in German, French and Swiss law.
Keywords: Consent of the third party for the conclusion of the contract, the validity of the contract, permit, approval.